2015
DOI: 10.1038/nature14277
|View full text |Cite
|
Sign up to set email alerts
|

Planet heating prevents inward migration of planetary cores

Abstract: Planetary systems are born in the disks of gas, dust and rocky fragments that surround newly formed stars. Solid content assembles into ever-larger rocky fragments that eventually become planetary embryos. These then continue their growth by accreting leftover material in the disc. Concurrently, tidal effects in the disc cause a radial drift in the embryo orbits, a process known as migration [1][2][3][4] . Fast inward migration is predicted by theory for embryos smaller than three to five Earth masses [5][6][7… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
201
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(213 citation statements)
references
References 25 publications
12
201
0
Order By: Relevance
“…Benítez-Llambay et al 2015Baruteau & Masset 2013;Pierens et al 2012;Lega et al 2014Lega et al , 2015Masset & Velasco 2016). Likely the planet temperature has even higher effect on satellite migration, as it affects the entire circumplanetary gas.…”
Section: Subdisk Mass and Density Of The 3-10 Jupiter-mass Planetsmentioning
confidence: 99%
See 1 more Smart Citation
“…Benítez-Llambay et al 2015Baruteau & Masset 2013;Pierens et al 2012;Lega et al 2014Lega et al , 2015Masset & Velasco 2016). Likely the planet temperature has even higher effect on satellite migration, as it affects the entire circumplanetary gas.…”
Section: Subdisk Mass and Density Of The 3-10 Jupiter-mass Planetsmentioning
confidence: 99%
“…3.2 we already mentioned that the different planet temperature affects the gas temperature even beyond the the subdisk. In the case of low mass planets, Benítez-Llambay et al (2015) showed that the planet luminosity alters the torque, which determines the migration of the planet inside the circumstellar disk. In the case of giant planets, the torque also drives the gap-opening, hence the change in planet temperature/luminosity can affect the gap properties.…”
Section: Subdisk Velocity Of the 3-10 Jupiter-mass Planetsmentioning
confidence: 99%
“…From this, several authors used an ad-hoc factor to reduce the type I migration rates to reproduce the observations (Alibert et al 2005;Ida & Lin 2008;Miguel et al 2011b,a). Moreover, if more realistic protoplanetary disks are assumed (Kley & Crida 2008;Paardekooper et al 2010Paardekooper et al , 2011Guilet et al 2013) or a more refined treatment of the accretion process of solid material by an embryo is considered (Benítez-Llambay et al 2015), the type I migration could substantially change and lead to a more complex problem. In order to not complicate our model, we do not include the effects of the type I migration and thus, we consider the in situ formation of the planetary embryos in all our simulations.…”
Section: Semi-analytical Model: Gaseous Phasementioning
confidence: 99%
“…In reality, planetary migration will occur simultaneously with planetary growth. Recently, Benítez-Llambay et al (2015) have numerically investigated the effect of planetary accretion on type I migration. They have shown that, when the solid accretion rate onto planets is high enough, the resultant accretion luminosity of planets can modify the density and thermal structure of disks especially in the vicinity of the planets.…”
Section: Planetary Migrationmentioning
confidence: 99%